Expression of inhibitory neurotransmitter gabaa receptors in human dental pulp: a potential role in dental nociceptive signalling - Sivakumar, Diveyaa (2023)
Dental pain is a prevalent and distressing condition that can have a significant impact on a person's daily life. It can arise from various causes, including dental diseases and conditions, as well as during dental treatments. Development of effective pain management strategies in the dental setting remains a challenge due to the unclear mechanisms of pain signalling in the dental pulp. Gamma-aminobutyric acid (GABA) is the main inhibitory neurotransmitter in the mammalian central nervous system (CNS) and has a well-established role in pain signalling. While several studies have explored the expression GABA and its receptors in the dental pulp, the exact influence of these receptors on dental pain signalling is still not fully understood. Therefore, this study aimed to investigate the gene and protein expression of the two most abundantly expressed GABAA receptor subunits, α1 and β2, in the healthy human dental pulp. In order to achieve the objective of the study, techniques such as RNA isolation, reverse transcription-polymerase chain reaction (RT-PCR) and immunohistochemistry (IHC) were employed. Prior to performing RT-PCR, the annealing temperature for amplification of both target genes were found to be 55°C. Gene expression analysis using RT-PCR demonstrated the presence of GABRA1 and GABRB2 in the dental pulp, and independent T-test analysis indicated that the expression of GABRA1 was significantly higher than GABRB2. Immunohistochemical staining provided visual evidence of GABRA1 and GABRB2 protein expression in the odontoblast layer of dental pulp, indicating their presence in cell bodies and odontoblastic processes extending into the dentin. Optimal IHC staining results were obtained by using Tris- EDTA (TE) buffer at pH9 for antigen retrieval with antibody concentrations of 1:50 and 1:200 for the GABRA1 and GABRB2 antibodies, respectively. These findings support the hypothesis that GABAA receptor α1 and β2 subunits are expressed in human dental pulp. The presence of gene and protein expression of these subunits offers valuable insights for further research into the potential roles of GABAA receptors in dental related pain signalling. Future studies using diseased samples and functional investigations are warranted to explore the precise mechanisms and implications of GABAA receptor α1 and β2 subunits in dental pain and their potential therapeutic applications.